2009
DOI: 10.1016/j.canep.2009.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Examining the association between cigarette smoking and colorectal cancer using historical case–control data

Abstract: BACKGROUND The majority of recent, well-designed studies have shown that long-term cigarette smoking increases colorectal cancer risk, but older studies with shorter durations of exposure often found no association. This study aimed to examine colorectal cancer risk by smoking exposure using data collected in the late 1950s and early 1960s. METHODS This case-control study examined colorectal cancer risk by lifetime smoking history. There were 1,365 patients who visited Roswell Park Cancer Institute (RPCI) be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 65 publications
1
7
0
1
Order By: Relevance
“…Additionally, Wu et al (1987) showed that smokers had higher risks of CRC than non-smokers but not as high as ex-smokers. On the other hand, Peppone et al (2009) showed no association between long-term cigarette smoking and CRC risk.…”
Section: Discussionmentioning
confidence: 80%
“…Additionally, Wu et al (1987) showed that smokers had higher risks of CRC than non-smokers but not as high as ex-smokers. On the other hand, Peppone et al (2009) showed no association between long-term cigarette smoking and CRC risk.…”
Section: Discussionmentioning
confidence: 80%
“…These can be explained by difference in size of population, various background risk of the cancer, and prevalence of secondhand smoking in each country. In many studies, there are risk factors other than tobacco smoke associated with cancers such as diet, body mass index (BMI), and alcohol consumption (Peppone et al, 2009;Peppone et al, 2010) are not included in the research model and thus have the potential to cause bias towards the results of the study, included in this study which is became one of our limitations. Secondly, RRs used in our analysis were not limited to ASEAN population.…”
Section: Resultsmentioning
confidence: 99%
“…However, the relationship between smoking/smoking habits and the incidence of CRC was not confirmed [38]. Similarly, the results of a case study in the US surprisingly showed little relationship between long-term smoking and increased risk of CRC [39]. Nonetheless, smoking exacerbates many health issues in today's society, and its involvement should not be ignored.…”
Section: Discussionmentioning
confidence: 97%